PROMOTIF DAN PREVENTIF ANEMIA PADA IBU HAMIL DI KELURAHAN PAMPANGAN NAN XX KECAMATAN LUBUK BEGALUNG KOTA PADANG - Yusrawati Yusrawati; Aldina Ayunda Insani; Adela Resa Putri; Annisa Namirah Nasution; Aulia Echi Ramadhani; Suci Padma Risanti; Wilfa Muslimah Sihaloho; Wiwie Putri Adila; Yaumil Fuziah; Desmawati Desmawati; Vaulinne Basyir; Hudila Rifa Karmila (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
Anemia in pregnancy can disrupt the process of growth and development of the fetus. The need for iron increases exponentially during pregnancy, to meet the increased demand for the fetoplacental unit, causing pregnant women to be at high risk of developing anemia. The high incidence of anemia in RW I Pampangan Nan XX Village, Lubuk Begalung District, needs to be taken to find out the causal factors so that promotive and preventive action innovations can be carried out on the incidence of anemia in the community. One of them is the class for pregnant women online. The activity was carried in ampangan Nan XX Village, Lubuk Begalung District. The respondents in this activity were all pregnant women who were in RW I, Pampangan Nan XX Village, Lubuk Begalung District, totaling 8 people. From the results of data collection, it is known that 62.5% of pregnant women are anemic. Data analysis showed that there were two factors related to the incidence of anemia in pregnant women in RW 01, namely the mother's employment status (p = 0.018) and the gap of pregnancy (p = 0.018). Results in-depth interview shows that the current pandemic conditions have stopped classes for pregnant women and the community's economy has declined so that access to information about pregnancy is very limited. Classes for pregnant women are carried out online, using media such as groups on WhatsApp to facilitate information both before and after the implementation of online pregnant women classes. Information with ppt and video media can increase the understanding of pregnant women regarding the anemia information conveyed. It is hoped that health workers will be able to take advantage of the continued program that has been formed so that pregnant women can get good information about pregnancy, especially about the prevention of anemia.